Organization of The Process of Teaching Left-Handed Children in Primary School - Berdikhanova G; Sadikova G; Kendjaeva D; Yakupbaeva M; Omarova A; Tursunbaeva M (Indonesian Journal of Innovation Studies, 2022)
There is an ambiguous attitude towards left-handedness in society, some consider it a serious disadvantage, others - a manifestation of genius. The existence of such extreme points of view indicates that this phenomenon is poorly understood. The relevance of the chosen topic lies in the fact that left-handed children are increasingly found in the practice of modern primary schools, work with whom until recently was aimed at retraining, adjusting them to a common standard, but now psychologists and teachers have studied in more detail the nature of left-handedness and came to the conclusion that retraining can adversely affect the child’s psyche.